2012
DOI: 10.1002/ibd.22958
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis reveals transcriptome and microRNA signatures and drug repositioning targets for IBD and other autoimmune diseases

Abstract: This study presents a clinically relevant gene-level portrait of IBD subtypes and their connectivity to autoimmune diseases. The study identified candidates for repositioning of existing drugs to manage IBD. Integration of mice and human data point to an altered B-cell response as a cause for upregulation of genes in IBD involved in other aspects of immune defense such as interferon-inducible responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
33
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 94 publications
6
33
1
Order By: Relevance
“…To the best of our knowledge, the current study provides the first evidence demonstrating that SOX9 may promote osteosarcoma cell growth by down-regulating CLDN8 expression. Bioinformatic analysis demonstrated that CLDN8 was decreased in inflammatory bowel disease (Clark et al 2012). Moreover, the expression of CLDN8 mRNA is down-regulated in tumor tissues (Gröne et al 2007), and CLDN8 has been revealed as a candidate biomarker for the diagnosis in renal cell carcinoma and renal oncocytoma (Kim et al 2009;Osunkoya et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the current study provides the first evidence demonstrating that SOX9 may promote osteosarcoma cell growth by down-regulating CLDN8 expression. Bioinformatic analysis demonstrated that CLDN8 was decreased in inflammatory bowel disease (Clark et al 2012). Moreover, the expression of CLDN8 mRNA is down-regulated in tumor tissues (Gröne et al 2007), and CLDN8 has been revealed as a candidate biomarker for the diagnosis in renal cell carcinoma and renal oncocytoma (Kim et al 2009;Osunkoya et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18] In this study, we identified miR-31, miR-146a, miR-206, and miR-424 as novel miRNA biomarkers that are commonly and specifically expressed in the freshfrozen tissue of colonic mucosa from inflammatory bowel disease patients compared with colonic mucosa control patients. The dysregulated expression of four miRNAs in both ulcerative colitis and Crohn disease suggests that these miRNAs might be involved in the regulation of the common pathophysiological pathway leading to inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%
“…21,23,26,27 The genes which demonstrated the largest alteration in expression were associated with epithelial integrity such as CLDN8 and Paneth cell metaplasia (DEFA5, DEFA6, and REG1). The majority of genes reported to be associated with UC in previous studies are attributable to chronic inflammation and leukocyte infiltration into the mucosal tissue such as the SAA1 (serum amyloid A1), chemokine (C-X-C motif) ligands (CXCL6, CXCL11, CXCL13), and the matrix metallopeptidases (MMP1, MMP3, MMP12).…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28][29] In the vast majority of these studies, the samples were obtained from chronically inflamed tissue such that transcriptomic differences observed have been dominated by the consequences of tissue damage and the presence of infiltrating inflammatory cells. 21,24,26,27 A recent meta-analysis of a number of these studies 23 identified the tight junction molecule, claudin 8 (CLDN8), to be the most underexpressed gene in the colon in individuals with IBD. CLDN8 is a "barrier" tight junction molecule located in the apical part of the paracellular junction, 30 and thought to play a role in preventing paracellular back leakage of sodium.…”
mentioning
confidence: 99%
See 1 more Smart Citation